Estimation of 18S Gene Copy Number in Marine Eukaryotic Plankton Using a Next-Generation Sequencing Approach - Gong, Weida; Marchetti, Adrian (Frontiers in Marine Science, 2019)
The small subunit 18S rRNA (18S) gene is the most commonly used marker for taxonomic identification in eukaryotes. However, protists may harbor substantial variation in their 18S gene copy number, which can lead to a rapid decline in concordance between 18S gene sequences and actual organismal abundances. Here we used a computational method to estimate 18S gene copy number in seven species of marine eukaryotic phytoplankton and found strong interspecies and strain-level differences across and within the examined species. Our results emphasize that variations in 18S gene copy number need to be taken into consideration and that corrections can improve the accuracy of quantitative eukaryotic microbial community profiles.